Genetic, nongenetic and epigenetic risk determinants in developmental programming of type 2 diabetes. (30th September 2014) - Vaag, Allan; Brøns, Charlotte; Gillberg, Linn; Hansen, Ninna S.; Hjort, Line; Arora, Geeti P.; Thomas, Nihal; Broholm, Christa; Ribel‐Madsen, Rasmus; Grunnet, Louise G.
Abstract Low birthweight (LBW) individuals and offspring of women with gestational diabetes mellitus (GDM) exhibit increased risk of developing type 2 diabetes (T2D) and associated cardiometabolic traits in adulthood, which for both groups may be mediated by adverse events and developmental changes in fetal life. T2D is a multifactorial disease occurring as a result of complicated interplay between genetic and both prenatal and postnatal nongenetic factors, and it remains unknown to what extent the increased risk of T2D associated with LBW or GDM in the mother may be due to, or confounded by, genetic factors. Indeed, it has been shown that genetic changes influencing risk of diabetes may also be associated with reduced fetal growth as a result of reduced insulin secretion and/or action. Similarly, increased risk of T2D among offspring could be explained by T2D susceptibility genes shared between the mother and her offspring. Epigenetic mechanisms may explain the link between factors operating in fetal life and later risk of developing T2D, but so far convincing evidence is lacking for epigenetic changes as a prime and direct cause of T2D. This review addresses recent literature on the early origins of adult disease hypothesis, with a special emphasis on the role of genetic compared with nongenetic and epigenetic risk determinants and disease mechanisms.